In Vivo Treatment with a Standardized Green Tea Extract Restores Cardiomyocyte Contractility in Diabetic Rats by Improving Mitochondrial Function through SIRT1 Activation - Rocchina Vilella; Simona Izzo; Valeria Naponelli; Monia Savi; Leonardo Bocchi; Cristina Dallabona; Maria Carla Gerra; Donatella Stilli; Saverio Bettuzzi (MDPI AG, 2022)
Background. Green tea catechins are known to promote mitochondrial function, and to modulate gene expression and signalling pathways that are altered in the diabetic heart. We thus evaluated the effectiveness of the in vivo administration of a standardized green tea extract (GTE) in restoring cardiac performance, in a rat model of early streptozotocin-induced diabetes, with a focus on the underlying mechanisms. Methods. Twenty-five male adult Wistar rats were studied: the control (n = 9), untreated diabetic animals (n = 7) and diabetic rats subjected to daily GTE administration for 28 days (n = 9). Isolated ventricular cardiomyocytes were used for ex vivo measurements of cell mechanics and calcium transients, and molecular assays, including the analysis of functional protein and specific miRNA expression. Results. GTE treatment induced an almost complete recovery of cardiomyocyte contractility that was markedly impaired in the diabetic cells, by preserving mitochondrial function and energy availability, and modulating the expression of the sarcoplasmic reticulum calcium ATPase and phospholamban. Increased Sirtuin 1 (SIRT1) expression and activity substantially contributed to the observed cardioprotective effects. Conclusions. The data supported the hypothesis that green tea dietary polyphenols, by targeting SIRT1, can constitute an adjuvant strategy for counteracting the initial damage of the diabetic heart, before the occurrence of diabetic cardiomyopathy.